Unraveling : remaking personhood in a neurodiverse age - Wolf-Meyer, Matthew J. (University of Minnesota Press, 2020)
"Developing a cybernetic model of subjectivity and personhood that honors disability experiences to reconceptualize the category of the human. Twentieth-century neuroscience fixed the brain as the basis of consciousness, the self, identity, individuality, even life itself, obscuring the fundamental relationships between bodies and the worlds that they inhabit. In Unraveling, Matthew J. Wolf-Meyer draws on narratives of family and individual experiences with neurological disorders, paired with texts by neuroscientists and psychiatrists, to decenter the brain and expose the ableist biases in the dominant thinking about personhood. Unraveling articulates a novel cybernetic theory of subjectivity in which the nervous system is connected to the world it inhabits rather than being walled off inside the body, moving beyond neuroscientific, symbolic, and materialist approaches to the self to focus instead on such concepts as animation, modularity, and facilitation. It does so through close readings of memoirs by individuals who lost their hearing or developed trauma-induced aphasia, as well as family members of people diagnosed as autistic-texts that rethink modes of subjectivity through experiences with communication, caregiving, and the demands of everyday life. Arguing for a radical antinormative bioethics, Unraveling shifts the discourse on neurological disorders from such value-laden concepts as 'quality of life' to develop an inclusive model of personhood that honors disability experiences and reconceptualizes the category of the human in all of its social, technological, and environmental contexts."--